Effect of nutrient reductions on dissolved oxygen and pH: a case study of Narragansett bay - Wang, Hongjie; Codiga, Daniel L.; Stoffel, Heather; Oviatt, Candace; Huizenga, Kristin; Grear, Jason (Frontiers in Marine Science, 2024)
To assess the consequences of nutrient reduction strategies on water quality under climate change, we investigated the long-term dynamics of dissolved oxygen (DO) and pH in Narragansett Bay (NB), a warming urbanized estuary in Rhode Island, where nitrogen loads have declined due to extensive wastewater treatment plant upgrades. We use 15 years (January 2005-December 2019) of measurements from the Narragansett Bay Fixed Station Monitoring network. Nutrient-enhanced phytoplankton growth can increase DO in the upper water column while subsequent respiration can reduce water column DO and enhance bottom water acidification, and vice-versa. We observed significant decreases in surface DO levels, concurrent with a significant increase in bottom DO, associated with the nitrogen load reduction. Surface DO decline was primarily attributed to reduced intensity of primary productivity, supported by a concurrent decrease in surface chlorophyll concentrations. Meanwhile, the influence of reduced organic matter respiration led to the increase of bottom DO levels by 9 µmol kg-1 (approximately 0.2 mg L-1 for typical summer temperature and salinity) over a 15-year period, which overcame the opposite influence of oxygen reduction from solubility decreases due to warming temperatures. In contrast, long-term changes in surface pH have not exhibited discernible trends beyond natural variability, likely due to the complex and sometimes opposing influences of biological activity and changing river flow conditions. We observed a slight increase in bottom pH, associated with the increase in DO in bottom water. Notably, future variations in freshwater discharge, particularly linked to extreme precipitation events, may further influence water carbonate chemistry and thereby impact pH dynamics. This study highlights the necessity of long-term time series measurements in helping understand the impacts of environmental management practices in improving water quality in coastal regions during a changing climate.